Hubungan Pemanfaatan Buku Kia dengan Pengetahuan Ibu Hamil Tentang Perawatan Kehamilan di BPM Riris Indayani S.Tr.Keb - Umniatuz Zakiyah; Mega Silvian Natalia; Tutik Ekasari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The MCH handbook This book covers a wide range of health-related subjects for parents, beginning with pregnancy and continuing through delivery and maturity. It also provides several techniques to take care of your own health as well as the health of your children. Therefore, if the KIA book is not helpful, it would be terrible to be able to notice it on the mother and kid. A number of factors, including the comprehension of Abu Hamil, have the potential to influence the interpretation of the book KIA. Acquiring knowledge may be accomplished via education, experience, or the information that one already has. The purpose of this research is to investigate the connection between the use of the KIA book and the level of knowledge that the parents of Hamil children have on child care at Bpm Riris indayani S.Tr. Keb. This particular study is a research endeavour that focusses on analytical observational research. An alternative approach, known as a cross-sectional design, is used. Due to the fact that they all had KIA books in hand throughout the time period of April to June 2023, this study included the participation of twenty-four married women. Through the use of a method known as comprehensive sampling, we conducted a survey of the whole population for this research. Instruments that are used include a KIA bookcase as well as a kuisoner. A mother who went to bpm with KIA books was the subject of the data gathering that was carried out under this project. The techniques of data analysis that have been chosen are the univariate analysis and the bivariate analysis. Based on the findings of the study, it was discovered that out of a total of 24 respondents, 87.5% were aware of health insurance, and 21 respondents were also aware of disability insurance. Given the p-value of.002 obtained from the chi-square statistical test, where the α-value is 0.05, it is possible for us to draw the conclusion that there is a Hubungan Pemanfaatan Buku KIA Dengan Pengetahuan Ibu Hamil Tentang Perawatan Kehamilan Di BPM Riris Indayani S.Tr. Keb. The recommendation for the elderly person is to learn about the book of KIA that is distributed in a healthy manner.